Meziválečná americká sociologie v obrazech: Fotoalbum Otakara Machotky - Nešpor, Zdeněk R. (Lidé města, 2023)
The author presents fifteen photographs from the private album of Otakar Machotka (1899–1970), taken of prominent American sociologists and social scientists hailing from the interwar era. Machotka was one of the key personalities of Czech sociology in the given period, striving for its empiricization and internationalization, while at the same time he was an excellent expert on American and French sociology. He published a study on American sociology (1937) based on a research stay in Chicago and Los Angeles (and on his travels throughout the United States) in 1934–35. The photographs, which are published here for the first time, were taken at the same time. Although for methodological reasons we cannot consider them a sociological resource in the full sense, they provide interesting insight into the elite of the field at the time. The portraits are accompanied by short biographies, written by the publisher.